Targeted therapies and molecular targets in the therapeutic landscape of advanced urothelial carcinoma: state of the art and future perspectives - Irene Testi; Giulia Claire Giudice; Giuseppe Salfi; Martino Pedrani; Sara Merler; Fabio Turco; Luigi Tortola; Ursula Vogl (Open Exploration Publishing Inc., 2024)
Advanced urothelial carcinoma (aUC) has a dismal prognosis, with a 5-year survival rate of approximately 10%. Platinum-based chemotherapy has been the backbone of the first-line treatment of aUC for over 40 years. Only in the last decade, the treatment of aUC has evolved and been enriched with new classes of drugs that demonstrated pivotal improvements in terms of oncological responses and, ultimately, survival. Thus, the approach to aUC is becoming more and more tailored to the single patient, particularly owing to targeted therapies, such as fibroblast growth factor receptor (FGFR) inhibitors, antibody-drug conjugates (ADCs) targeting TROP2 and Nectin-4, anti-Her-2 therapies and others. However, due to the rapidly evolving scenario, the optimal sequence of systemic treatment is unknown and several important research questions remain unanswered, including the identification of reliable biomarkers to guide treatment decisions. Through ongoing research and clinical trials, we can continue to refine personalized treatment strategies and ultimately enhance patient care in this challenging disease setting. In this review, we provide a comprehensive overview of the current and emerging landscape of targeted therapies for aUC. We delved into the opportunities and challenges presented by personalized treatment approaches and explored potential future directions in this rapidly evolving field.